IP Storage Networking: Straight to the Core - Orenstein, Gary (Addison Wesley, 2011)
IP Storage Networking: Straight to the Core is your complete blueprint for planning, deploying, managing, and maximizing the business value of enterprise storage. Gary Orenstein introduces IP storage, iSCSI, and related technologies; then shows how to integrate them into an overall storage strategy for maximizing availability and business agility. Coverage includes: architecture; software infrastructure; virtualization; security; storage policies; outsourcing; and measuring ROI on enterprise storage